Experimental study of corner separation and unsteady characteristics in linear compressor cascades with and without sweeping jet actuator - S.W. Chen; W.H. Li; C. Xu; Q.H. Meng (Propulsion and Power Research, 2024)
Sweeping jet actuator (SJA) has been widely applied for active flow control in open flows. In this paper, the SJA character in compressor cascade and its performance for separation control in inner flows are discussed. Time-averaged and transient flow field measurement, together with visualization methods are utilized. It is found that endwall effects are important for both SJA behaviors and SJA performance for separation control in compressor cascades. There is a maximum of 12.7% total pressure loss reduction with SJA placed near the separation position, close to the endwall and under appropriate flowrate. The characteristic frequencies in the flow field contribute to the capture of influence regions of vortices and excitation jets. Two concentrated shedding vortices and SJA jets impact region helped to judge that SJA energizes low momentum fluids in a large region and matches the high loss core well. To be concrete, the flow separation control mechanism of SJA lies on the interruption of the blade suction surface boundary layer development and the restriction of the lifting of the boundary layer from endwall towards blade suction surface.